Estudo da solidificação, refusão a laser, propriedades mecânicas e resistência ao desgaste de ligas AlSi10MgXNi (X=0,1,2,3) - Moura, Danusa Araújo de (2024)
The AlSi10Mg alloys play a significant role in industries such as aerospace, automotive, and microelectronics due to a combination of properties and characteristics, including low density, good mechanical properties, corrosion resistance, and affordable application cost. Although widely used, there is still room for improvement in their mechanical properties. In this context, the present study aimed to investigate the influence of Ni addition (1, 2, and 3% by weight) on directionally solidified (DS) AlSi10Mg alloy, at lower cooling rates, and laser surface remelted (RSL) alloy, at higher rates, on microstructure, tensile strength, hardness, nanohardness, and wear resistance. Cooling rates were determined for DS samples and estimated by extrapolation for RSL samples. α-Al dendritic arrangements were found in the microstructure of all tested alloys (DS and RSL), surrounded by the eutectic constituent. The microstructure of quaternary alloys consisted of α-Al+Si+Al3Ni phases, with Al3Ni having a predominant fishbone morphology found in higher proportions due to slow cooling and increased Ni content. The AlSi10Mg-1Ni alloy showed the best tensile results, reaching 4.6% elongation and a strength of 208 MPa, attributed to fine dendritic spacing (< 18 μm) and a mixture of Al3Ni with fishbone and plate morphology. Phase clusters identified in the melt pools were related to α-Al, Al+Si, and Al+Si+Al3Ni constituents. Overall, the melt pool hardness increased with higher Ni content, due to an increase in the Al3Ni intermetallic fraction. The AlSi10Mg-1Ni alloy exhibited the highest wear resistance among all DS samples in the short-term wear test (10 min/0.5 N), while RSL samples showed similar wear.